Patients' and rheumatologists' perspectives on the efficacy and safety of low-dose glucocorticoids in rheumatoid arthritis—an international survey within the GLORIA study. (4th January 2021) - Santiago, T; Voshaar, M; de Wit, M; Carvalho, P D; Buttgereit, F; Cutolo, M; Paolino, S; Castelar Pinheiro, G R; Boers, M; Da Silva, J A P
Abstract: Objective: To evaluate the current perspectives of patients and health professionals regarding the efficacy and safety of low-dose glucocorticoids (GCs) in RA. Methods: Two online surveys were disseminated to patients and health professionals, in their native language, through national patient organizations and national rheumatology medical societies, respectively. SurveyMonkey ®, MediGuard.org and the Glucocorticoid Low-dose Outcome in RA Study (GLORIA) website were used to offer and deliver these surveys. Results: A total of 1221 RA patients with exposure to GCs, and 414 rheumatologists completed the surveys. Patients and rheumatologists reported high levels of agreement regarding the efficacy of low-dose GCs: at least 70% considered that they are very rapid and effective in the control of signs and symptoms of RA. However, half of the patients also reported having suffered serious adverse events with GCs, and 83% described concerns about safety. The majority of rheumatologists estimated that endocrine, ophthalmologic and cutaneous adverse events affect >4% of all patients treated with low-dose GCs for 2 years, based on a heat map. Conclusions: RA patients with self-reported exposure to GCs express high levels of satisfaction with low-dose GCs efficacy, as do rheumatologists. However, both expressed excessive concerns regarding the safety of GCs (greatly exceeding the published evidence data), which may compromise the optimal use of this medication. This study indicates that there is an unmet need for appropriately designed prospective trials that shed light on the real risk associated with low-dose GCs, as well as a need for renovated educational programs on the real benefits and harms of low-dose GCs, for both patients and physicians.